FRI0588 Interim results of a phase 2 study of XMAB®5871, a reversible B cell inhibitor, in IGG4-related disease. (15th June 2017) - Stone, JH; Wallace, ZS; Perugino, CA; Fernandes, AD; Patel, PS; Foster, PA; Zack, DJ
Abstract : Background: IgG4-related disease (IgG4-RD) is an immune-mediated condition causing fibro-inflammatory lesions that can lead to irreversible organ damage. No approved therapies for IgG4-RD exist. We report the use of a novel monoclonal antibody, XmAb5871, in IgG4-RD. XmAb5871 is a humanized anti-CD19 antibody with an Fc portion engineered for increased affinity (up to 400-fold over native IgG1 ) to FcgRIIb, the only Fc receptor on B cells. Co-ligation of CD19 and FcgRIIb leads to inhibition of B lineage cells bearing these targets. Reversible inhibition of B cell function without B cell ablation is one potential advantage of this approach. Methods: The trial is an open-label investigation of XmAb5871 in active IgG4-RD, defined by an IgG4-RD Responder Index (RI) of ≥3. XmAb5871 (5 mg/kg) is administered IV every 14 days for 12 doses. The primary outcome measure is the proportion of patients on day 169 (2 weeks following the last dose) with a decrease in the IgG4-RD RI of 2 or more points compared to baseline. Glucocorticoids are permitted but not required at entry and must be discontinued by two months. Other immunosuppressive medications are not allowed. Imaging and mechanistic studies are performed at baseline and at selected intervals. Results: Fifteen patients were enrolled between March 2016 and January 2017. As of October 31, 2016, 12 patients had received at least one infusion of XmAb5871. The median age of the 12 patients is 58 years (range: 43 to 78 years). Two-thirds of the patients are male. Nine of the 12 patients had elevated serum IgG4 concentrations at baseline with a mean serum IgG4 of 499 mg/dL (range: 25–2415; normal <86 mg/dL). The median baseline IgG4-RD RI score was 10 (range: 2–30), with active inflammatory disease in at least one organ system (median 4, range: 1–10). The organs most commonly affected were lymph nodes (75% of patients), submandibular glands (67%), parotid glands (58%), and lacrimal glands (50%). Four patients (33%) had kidney involvement and 3 (25%) had heart/pericardium findings. Nine of 11 patients (82%) have had an initial response to XmAb5871 therapy of at least a three-point reduction in the IgG4-RD RI within two weeks of the first dose. As of Oct 31st, 2016, five patients attained disease remission (an IgG4-RD RI of 0 and no prednisone treatment after 2 months) during the study. Efficacy outcomes will be updated as more patients complete the study. One patient had been on glucocorticoid treatment for 2 years and was on prednisone of 15 mg/day at baseline, but was able to discontinue prednisone by 2 months after starting treatment. Three patients experienced minor, transient gastrointestinal side-effects during the 1st infusion. One patient had infusion-related GI symptoms on the 5thinfusion and subsequently developed rash and arthritis. She was found to have anti-drug antibodies and has discontinued the study. Mechanistic studies show that both peripheral B cells and plasmablasts decrease substantially following therapy in the majority of patients. Studies of the mechanism of this decrease and functional B cell assays are under way. Conclusions: XmAb5871 is tolerated well in patients with active IgG4-RD and is a promising treatment approach for IgG4-RD. Disclosure of Interest: J. Stone Grant/research support from: Genetech/Roche, Xencor, Consultant for: Genentech/Roche, Xencor, Z. Wallace: None declared, C. Perugino: None declared, A. Fernandes: None declared, P. Patel: None declared, P. Foster Shareholder of: Full time employee of Xencor, Employee of: Full time employee of Xencor, D. Zack Shareholder of: Full time employee of Xencor, Employee of: Full time employee of Xencor